2020
DOI: 10.1007/s00268-020-05841-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of In‐Hospital Mortality in Surgical Wards: A Multivariable Retrospective Cohort Analysis of 2,800,069 Hospitalizations

Abstract: Background Identifying prognostic factors that are predictive of in-hospital mortality for patients in surgical units may help in identifying high-risk patients and developing an approach to reduce mortality. This study analyzed mortality predictors based on outcomes obtained from a national database of adult patients. Materials and methods This retrospective study design collected data obtained from the National Health Fund in Poland comprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The in-hospital mortality during surgery was recently reported to be lower in women than men. 41,691 In contrast, among 609 735 patients who underwent elective NCS between 2009 and 2016, the odds of post-operative 90 day mortality were higher among women with HF than men with HF. 692 Further studies are needed to provide more information about outcome differences between men and women in NCS.…”
Section: Sex Differencesmentioning
confidence: 99%
“…The in-hospital mortality during surgery was recently reported to be lower in women than men. 41,691 In contrast, among 609 735 patients who underwent elective NCS between 2009 and 2016, the odds of post-operative 90 day mortality were higher among women with HF than men with HF. 692 Further studies are needed to provide more information about outcome differences between men and women in NCS.…”
Section: Sex Differencesmentioning
confidence: 99%
“…The results of prior studies on this topic are conflicting. Two extensive studies from Canada and Poland reported statistically significantly lower mortality among females across various surgical procedures [ 23 , 24 ]. An American study also found significantly lower postoperative sepsis rates among females, but the relationship between sex and mortality was not evaluated [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, ascertainment of longer-term outcomes allows for the added ability to capture variation in outcomes due to both psychosocial factors and biological differences. Previous studies with short term follow-up have identified that female sex is associated with a lower in-hospital mortality risk among patients undergoing cardiac and non-cardiac surgery [ 12 ] and that perioperative major adverse cardiovascular events occurred more among male patients [ 13 ]. Our study builds on these studies by evaluating longer-term post-operative outcomes and demonstrating a consistent increase in all-cause mortality and all-cause hospitalization among male patients.…”
Section: Discussionmentioning
confidence: 99%